In Vivo Removal of N-Terminal Fusion Domains From Recombinant Target Proteins Produced in Nicotiana benthamiana - Islam, Md Reyazul; Choi, Seoyoung; Muthamilselvan, Thangarasu; Shin, Kunyoo; Hwang, Inhwan (Frontiers in Plant Science, 2020)
Plants show great potential for producing recombinant proteins in a cost-effective manner. Many strategies have therefore been employed to express high levels of recombinant proteins in plants. Although foreign domains are fused to target proteins for high expression or as an affinity tag for purification, the retention of foreign domains on a target protein may be undesirable, especially for biomedical purposes. Thus, their removal is often crucial at a certain time point after translation. Here, we developed a new strategy to produce target proteins without foreign domains. This involved in vivo removal of foreign domains fused to the N-terminus by the small ubiquitin-related modifier (SUMO) domain/SUMO-specific protease system. This strategy was tested successfully by generating a recombinant gene, BiP:p38:bdSUMO : His:hLIF, that produced human leukemia inhibitory factor (hLIF) fused to p38, a coat protein of the Turnip crinkle virus; the inclusion of p38 increased levels of protein expression. The recombinant protein was expressed at high levels in the leaf tissue of Nicotiana benthamiana. Coexpression of bdSENP1, a SUMO-specific protease, proteolytically released His:hLIF from the full-length recombinant protein in the endoplasmic reticulum of N. benthamiana leaf cells. His:hLIF was purified from leaf extracts via Ni2+–NTA affinity purification resulting in a yield of 32.49 mg/kg, and the N-terminal 5-residues were verified by amino acid sequencing. Plant-produced His:hLIF was able to maintain the pluripotency of mouse embryonic stem cells. This technique thus provides a novel method of removing foreign domains from a target protein in planta.